Some Statistical Evidence on the Effects of Financial Innovation - Milbourne, Ross; Moore, H. Alec (The Review of Economics and Statistics, 1986)
sumer reliance upon advertising since these mechanisms substitute as sources of product/vendor information. One can predict, therefore, that when relative prices favor consumer reliance upon advertising as information, producers will respond accordingly. This prediction also received empirical verification-advertising intensity by sellers in the mobile Washington, D.C. area greatly exceeded advertising intensity in the relatively stable Baltimore, Maryland area.